O ensino de Filosofia e o uso das tecnologias digitais de informação e comunicação: um estudo com alunos do ensino médio sobre o desenvolvimento da autonomia a partir do pensamento kantiano. - ARAÚJO, Ediel dos Anjos (2019)
This dissertation was developed within the program of the Professional Master in Philosophy - PROFI-FILO, from the Federal University of Maranhão, linked to the research line Philosophy and Teaching Practice. The research aims first to conduct an investigation about the use of Digital Information and Communication Technologies - TDIC as a pedagogical resource for teaching philosophy in high school, from the perspective of Kantian autonomy. The research is exploratory and qualitative with bibliographic and documentary research and empirical research. The instruments used in the research were open and closed questionnaires and a semi-structured interview that served to collect data about the socio-cultural conditions of the subjects and the questions regarding the use of ICT as tools for the awakening of autonomy in the teaching of philosophy, in this case, from using the Nearpod application and the WebQuest methodology. The sample group consists of students from the third year of high school at the Federal Institute of Maranhão (IFMA), Campus São José de Ribamar. In the construction of the theoretical framework of analysis, the theoretical contribution of several authors was taken as reference. Among these, the following stand out: Bernardino (2015), Castanheira (2018), Castells (2003), Martino (2015), Pocho ( 2014), Kant (1986, 1993, 1999) and Westphalen (2007). Based on the hypothesis that ICT can contribute to the teaching of philosophy and to the process of constitution of student autonomy, this paper aimed to understand the act of philosophizing from a virtual agora, which eventually confirmed itself. , given that ICT can be great allies of the Philosophy teacher in the context of the student training process and for the development of Kantian autonomy.